A Poker Game Description Language - Castro Correia, Joao; Teofilo, Luis Filipe; Lopes Cardoso, Henrique; Reis, Luis Paulo (2013 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2013)
During the last decade, Computer Poker has become the preferred test-bed for validating developments on the extensive-form game and multi-agent systems research domains. Because Poker is a game with hundreds of variants differing from each other by their betting structure, number of cards in the deck or winning conditions, numerous agents have been created for several different variants of the game. However, there is not a single unified description model that allows for those agents to be tested across different Poker variants inexpensively. For this reason, we introduce the Poker Game Description Language (PGDL), which, unlike other incomplete information GDL's, is uniquely focused on Poker agent development and testing. PGDL is integrated into a playable system which not only makes available a basic Agent Development API in Prolog, but also provides a simple in-built agent which can adapt to user-defined rules. In addition, this framework has a simple GUI which both basic and advanced test subjects demonstrated to be adequate and easy-to-use when defining new PGDL instances. We believe that despite the existence of more generic general game playing systems, the fact that our language natively supplies a shared infrastructure, common to all Poker variants, renders our approach very pertinent for Poker agent development. Tests demonstrated that our language was capable of describing the most popular Poker variants.